Functional Chitosan-Based Composites - Marin, Luminita; Bardosova, Maria (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Functional chitosan-based composites provide recent advances in the field. This reprint explores the preparation and characterization of nanocomposite films, membranes, hydrogels and nanoparticles, emphasizing their potential application as medical devices, packaging, or fuel cells. It will be a useful resource for academic and industry scientists.